Marketing of Library & Information Products & Services: A Select Bibliography - Raja, M.U. (DESIDOC Journal of Library & Information Technology, 2003)
Marketing of Library & Information Products & Services : A select bibliography http://dx.doi.org/10.14429/dbit.18.3.3399